Ultralow thermal conductivity of thermoelectric compound Ag2BaGeSe4 - Y. X. Tang; A. J. Hong; W. J. Zhai; Y. Shao; L. Lin; Z. B. Yan; X. H. Zhou; X. M. Lu; C. Chen; X. P. Jiang; J.-M. Liu (AIP Advances, 2021)
Due to their relatively low but potentially promising conversion efficiency, great efforts have been made in exploration of new thermoelectric materials, where ultralow thermal conductivity is usually desired without scarifying the power factor (PF). Cu-based quaternary chalcogenides, such as Cu2ZnSnSe4 and its analogs, have long been considered potential candidates for thermoelectric applications, while Ag-based counterparts with potentially ultralow thermal conductivity have rarely been studied. In this work, we report the thermoelectric properties of the Ag-based compound Ag2BaGeSe4. A series of polycrystalline Ag2+xBa1−xGeSe4 samples with x = 0–0.1 were synthesized via the vacuum melting method, and indeed, an ultralow thermal conductivity of as low as ∼0.35 W m−1 K−1 was achieved. It is found that Ag doping does benefit from the enhancement of carrier density, but this enhancement may be partially offset by the serious hole-killer effect at low (room) temperature, as revealed in the literature. However, the moderately enhanced electrical conductivity at high temperature contributes to a PF of ∼1.9 μW cm−1 K−2 and a figure of merit (ZT) value of up to ∼0.33 at 673 K for sample x = 0.075. The first-principles calculation indicates the preference of low-lying optical modes and avoided crossing effects, together with the high Grüneisen parameter and short relaxation time, all contributing to the ultralow thermal conductivity of this series.